Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Media Papan Statistik Bagi Siswa Kelas VI SD Negeri 1 Bojanegara Sigaluh - Wahyu Nuria Handayani; Sri Haryanto; Firdaus (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
1) Assess the level of comprehension of the mean, median, and mode among students in class VI; 2) evaluate students' use of statistical board media in learning the average, median, and mode; and 3) evaluate students' improved learning outcomes as a result of this usage. This study employs a descriptive technique and a class action tactic. The research employs two standard cycles of action planning, action implementation, and reflection. The pre-cycle study's findings indicated a 40% accomplishment level with a 58.55 class average. Increase to 55% in cycle I with an average value of 63, and to 85% in cycle II with an average value of 75.65. Cycle II had a 12.65% gain, which is a significant plus. The study's finding indicates that class VI pupils at SD Negeri 1 Bojanegara Sigaluh may learn more effectively when visual aids are used.